Exploring the Impact of Board Attributes on ESG Scores of Indonesian Companies - Setiani, Eko Putri; Novitasari, Budi Tiara (Nominal: Barometer Riset Akuntansi dan Manajemen, 2024)
ABSTRACTThis study aims to examine the impact of board attributes on ESG (Environmental, Social, and Governance) scores.  The total sample used was 86 companies from 2019 to 2023, resulting in 433 firm-year observations. The dependent variable is the standardized ESG Score, a high score indicates excellent relative ESG performance and high degree of transparency in reporting material ESG data publicly.  The independent variables used are Sustainability Committee, Gender Diversity, and Board Meetings.  The findings of this study indicate that certain board attributes, specifically the presence of a sustainability committee within the company, gender diversity among board members, and the average overall attendance percentage of board meetings, positively influence ESG Scores.  Companies must pay attention to board attributes to improve their ESG Scores, encourage sustainable value creation, and foster stakeholder trust and confidence in their commitment to environmental, social, and governance excellence.Keywords: ESG Scores, Sustainability Committee, Gender Diversity, Board MeetingABSTRAKPenelitian ini bertujuan untuk menguji dampak atribut dewan terhadap skor ESG (Environmental, Social, and Governance). Total sampel yang digunakan sebanyak 86 perusahaan dari tahun 2019 sampai dengan 2023, sehingga menghasilkan 433 firm-year observations. Variabel dependen adalah Skor ESG yang terstandarisasi, skor yang tinggi menunjukkan kinerja ESG yang relatif sangat baik dan tingkat transparansi yang tinggi dalam pelaporan data ESG yang material kepada publik. Variabel independen yang digunakan adalah Komite Keberlanjutan, Keberagaman Gender, dan Rapat Dewan. Temuan penelitian ini menunjukkan bahwa atribut dewan tertentu, khususnya kehadiran komite keberlanjutan dalam perusahaan, keberagaman gender di antara anggota dewan, dan rata-rata persentase kehadiran keseluruhan rapat dewan, berpengaruh positif terhadap Skor ESG. Perusahaan harus memperhatikan atribut dewan untuk meningkatkan Skor ESG mereka, mendorong penciptaan nilai yang berkelanjutan, dan menumbuhkan kepercayaan dan keyakinan pemangku kepentingan terhadap komitmen mereka terhadap keunggulan lingkungan, sosial, dan tata kelola.Kata kunci: Skor ESG, Komite Sustainability, Keragaman Gender, Rapat Dewan